Alzheimer’s Disease: From Pathogenesis to Mesenchymal Stem Cell Therapy – Bridging the Missing Link - Hu, Jingqiong; Wang, Xiaochuan (Frontiers in Cellular Neuroscience, 2022)
Alzheimer’s disease (AD) is the most prevalent neurodegenerative disease worldwide. With the increasing trend of population aging, the estimated number of AD continues to climb, causing enormous medical, social and economic burden to the society. Currently, no drug is available to cure the disease or slow down its progression. There is an urgent need to improve our understanding on the pathogenesis of AD and develop novel therapy to combat it. Despite the two well-known pathological hallmarks (extracellular amyloid plaques and intracellular Neurofibrillary Tangles), the exact mechanisms for selective degeneration and loss of neurons and synapses in AD remain to be elucidated. Cumulative studies have shown neuroinflammation plays a central role in pathogenesis of AD. Neuroinflammation is actively involved both in the onset and the subsequent progression of AD. Microglia are the central player in AD neuroinflammation. In this review, we first introduced the different theories proposed for the pathogenesis of AD, focusing on neuroinflammation, especially on microglia, systemic inflammation, and peripheral and central immune system crosstalk. We explored the possible mechanisms of action of stem cell therapy, which is the only treatment modality so far that has pleiotropic effects and can target multiple mechanisms in AD. Mesenchymal stem cells are currently the most widely used stem cell type in AD clinical trials. We summarized the ongoing major mesenchymal stem cell clinical trials in AD and showed how translational stem cell therapy is bridging the gap between basic science and clinical intervention in this devastating disorder.